2021
DOI: 10.1111/1541-4337.12866
|View full text |Cite
|
Sign up to set email alerts
|

Undesirable discoloration in edible fish muscle: Impact of indigenous pigments, chemical reactions, processing, and its prevention

Abstract: Fish is rich in proteins and lipids, especially those containing polyunsaturated fatty acids, which made them vulnerable to chemical or microbial changes associated with quality loss. Meat color is one of vital criteria indicating the freshness, quality, and acceptability of the meat. Color of meat is governed by the presence of various pigments such as hemoglobin, myoglobin (Mb), and so on. Mb, particularly oxy‐form, is responsible for the bright red color of fish muscle, especially tuna, and dark fleshed fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 197 publications
(293 reference statements)
1
18
0
Order By: Relevance
“…The effect of fish meat ratios on color parameters was observed with increasing L*, a*, and b* values when salmon meat content increased. The orange color of salmon is due to carotenoids such as astaxanthin and canthaxanthin (Singh et al 2022), which are not found in white-fleshed fish, so the carotenoids content in salmon meat was possibly responsible for variation in color parameters. 22.2 ab ± 0.9 22.1 ± 0.7 23.7 ab ± 1.9 3 16.6 d ± 1.0 20.8 b ± 0.7 22.5 a ± 0.8 22.3 ± 0.7 23.9 ab ± 1.6 1 35°C 17.9 ab ± 0.8 20.4 c ± 0.9 22.3 a ± 0.5 22.3 ± 0.9 24.1 a ± 2.1 2 18.0 ab ± 0.8 21.2 b ± 1.0 22.4 a ± 1.0 22.4 ± 0.9 24.2 a ± 1.9 3 18.1 ab ± 0.8 21.7 a ± 0.8 22.8 a ± 0.9 22.4 ± 0.9 24.4 a ± 1.9 Hardness and chewiness decreased, whereas cohesiveness increased after retort processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of fish meat ratios on color parameters was observed with increasing L*, a*, and b* values when salmon meat content increased. The orange color of salmon is due to carotenoids such as astaxanthin and canthaxanthin (Singh et al 2022), which are not found in white-fleshed fish, so the carotenoids content in salmon meat was possibly responsible for variation in color parameters. 22.2 ab ± 0.9 22.1 ± 0.7 23.7 ab ± 1.9 3 16.6 d ± 1.0 20.8 b ± 0.7 22.5 a ± 0.8 22.3 ± 0.7 23.9 ab ± 1.6 1 35°C 17.9 ab ± 0.8 20.4 c ± 0.9 22.3 a ± 0.5 22.3 ± 0.9 24.1 a ± 2.1 2 18.0 ab ± 0.8 21.2 b ± 1.0 22.4 a ± 1.0 22.4 ± 0.9 24.2 a ± 1.9 3 18.1 ab ± 0.8 21.7 a ± 0.8 22.8 a ± 0.9 22.4 ± 0.9 24.4 a ± 1.9 Hardness and chewiness decreased, whereas cohesiveness increased after retort processing.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fish meat type ratios on color parameters was observed with increasing L *, a *, and b * values when salmon meat content increased. The orange color of salmon is due to carotenoids such as astaxanthin and canthaxanthin (Singh et al 2022), which are not found in white‐fleshed fish, so the carotenoids content in salmon meat was possibly responsible for variation in color parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish smoked by conventional smoking is carried out in a closed manner so that it does not come into contact with the open air, while non-conventional smoking techniques are carried out openly so that it is potentially contaminated with sources of histamine-producing bacteria. Handling is the main key in inhibiting the formation of histamine, discoloration, protein solubility, and microbial growth in skipjack tuna (Singh, Mittal, & Benjakul, 2021). Smoking fish is intended to maintain freshness, in the sense that it still meets the requirements for human consumption by preventing the occurrence of fish spoilage.…”
Section: The Effect Of Conventional and Non-conventional Smoking On The Histamine Content In Smoked Fishmentioning
confidence: 99%
“…In the canning tuna industry, the greening of tuna muscle has been reported as an anomaly of discoloration by thermal treatment. However, although there is no data available related to the economic impact, considering that tuna greening is an unwanted muscle pigmentation, this results in financial loss for this industry ( Singh, Mittal & Benjakul, 2022 ).…”
Section: Introductionmentioning
confidence: 99%